2022
DOI: 10.1155/2022/2782429
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin and Its Derivate Alleviate Pulmonary Hypertension and Vasoconstriction in Rodent Models

Abstract: Background. Pulmonary arterial hypertension (PAH) is a complex pulmonary vasculature disease characterized by progressive obliteration of small pulmonary arteries and persistent increase in pulmonary vascular resistance, resulting in right heart failure and death if left untreated. Artemisinin (ARS) and its derivatives, which are common antimalarial drugs, have been found to possess a broad range of biological effects. Here, we sought to determine the therapeutic benefit and mechanism of ARS and its derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…American Heart Association (AHA) and global healthcare practitioners recognize elevated SBP and DBP are among the risk factors of developing cardiac artery diseases (CAD) and cardiovascular diseases (CVD) ( Price et al, 2019 ; Naidu et al, 2022 ; Kittleson et al, 2023 ). In this study, it can be observed that blood flow restriction training intervention has beneficial effect on the regulation of blood pressure, especially through down-regulating SBP, probably through enhancing eNOS synthesis and promoting the secretion of nitric oxide (NO) to the blood vessels smooth muscle endothelial cells ( Li et al, 2020 ; Bao et al, 2022 ; Cai and Chen, 2022 ; Wu et al, 2022 ). Therefore, it is recommended for the elderly to practice blood flow restriction training under appropriate workload, which can be helpful in maintaining their regular blood pressure and have potential benefits in decreasing CAD and CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…American Heart Association (AHA) and global healthcare practitioners recognize elevated SBP and DBP are among the risk factors of developing cardiac artery diseases (CAD) and cardiovascular diseases (CVD) ( Price et al, 2019 ; Naidu et al, 2022 ; Kittleson et al, 2023 ). In this study, it can be observed that blood flow restriction training intervention has beneficial effect on the regulation of blood pressure, especially through down-regulating SBP, probably through enhancing eNOS synthesis and promoting the secretion of nitric oxide (NO) to the blood vessels smooth muscle endothelial cells ( Li et al, 2020 ; Bao et al, 2022 ; Cai and Chen, 2022 ; Wu et al, 2022 ). Therefore, it is recommended for the elderly to practice blood flow restriction training under appropriate workload, which can be helpful in maintaining their regular blood pressure and have potential benefits in decreasing CAD and CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The myocyte cross‐sectional area in the LV lateral‐mid free wall, including epicardial and endocardial layers, was ascertained in H&E‐stained histological images using Image‐Pro Plus 6.0 software 52 . Myocardial and perivascular fibrosis were detected in the sections with Masson's trichrome staining, and the blue collagen deposition area/total cross‐sectional area of the myocardium (%) was calculated as previously reported 48,53,54 …”
Section: Methodsmentioning
confidence: 99%
“…48,53,54 4 12. | Materials Apocynin (APO), diethyldithiocarbamic acid (DETC), dimethyl sulfoxide (DMSO), N′-nitro-L-arginine-methyl ester hydrochloride (L-NAME), N-acetyl-L-cysteine (NAC), and tempol were purchased from Sigma Chemical Co. Salusin-β peptide was synthesized by Shanghai Changxi Biological Technology Co., Ltd. Anti-salusin-β antibody was obtained from Cloud-clone, and control IgG antibody was provided by Proteintech.…”
mentioning
confidence: 99%
“…In recent years, its anti-angiogenic effects have attracted much attention. Various models have accumulated mounting evidence, demonstrating the involvement of inhibiting aberrant angiogenesis and corneal neovascularization in the actions of artemisinin and its derivatives [ [21] , [22] , [23] , [24] ]. Artemisinin reduced the proliferation, migration, and tube formation of HUVEC, as well as the expression of VEGFR1 and VEGFR2 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%